Breast cancer screening lacking effectiveness - Giard, R W; Bonneux, L G (Nederlands tijdschrift voor geneeskunde, 2001)
The recent Cochrane review on mammographic breast cancer screening disclosed no convincing reduction of breast cancer mortality, together with an increase in the number of aggressive treatments. Given this outcome, there no longer exists solid experimental evidence to support mass screening. In the Netherlands over 800,000 women are invited to participate in this activity yearly. Is this still justifiable? The final answer rests on the conclusions from the analyses carried out from three different perspectives. From the methodological viewpoint, a broad re-analysis is needed which also takes the long-term adverse effects of radiotherapy into account. From the tumourbiological perspective, whether 'early' diagnosis really has potential therapeutic consequences should be explored further. From a societal perspective, more detailed and balanced information is required, since expectations regarding the effect of screening are unrealistic. Given the preliminary outcomes of these analyses, there are now serious reservations as to whether continuation of screening is justified. Women should be informed about this matter promptly.